2017
DOI: 10.1186/s12865-017-0214-z
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte differentiation and macrophage priming are regulated differentially by pentraxins and their ligands

Abstract: BackgroundCirculating bone marrow-derived monocytes can leave the blood, enter a tissue, and differentiate into M1 inflammatory, M2a remodeling/fibrotic, or M2c/Mreg resolving/immune-regulatory macrophages. Macrophages can also convert from one of the above types to another. Pentraxins are secreted proteins that bind to, and promote efficient clearance of, microbial pathogens and cellular debris during infection, inflammation, and tissue damage. The pentraxins C-reactive protein (CRP), serum amyloid P (SAP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 87 publications
(134 reference statements)
0
33
0
Order By: Relevance
“…In addition to PS, late apoptotic neutrophils were shown to express also pentraxin 3 (PTX3) in their membranes ( 113 ). PTX3 was shown not only to enhance their phagocytic removal during inflammation ( 113 ) but also to induce the expression of CD169 in macrophages ( 114 ), a molecule that interferes with the development of an autoimmune response ( 115 ).…”
Section: Apoptotic Cells Trigger Anti-inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…In addition to PS, late apoptotic neutrophils were shown to express also pentraxin 3 (PTX3) in their membranes ( 113 ). PTX3 was shown not only to enhance their phagocytic removal during inflammation ( 113 ) but also to induce the expression of CD169 in macrophages ( 114 ), a molecule that interferes with the development of an autoimmune response ( 115 ).…”
Section: Apoptotic Cells Trigger Anti-inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…A n i m p o r t a n t m e c h a n i s m i n t h e t u m o u r microenvironment is the activation of circulating monocytes to enter the tumour, where they then differentiate and become tumour-associated macrophages (TAMs) under the influence of IL-4 and IL-10 secreted by the cancer cells (Pilling et al, 2017;Shao et al, 2016). Overall, TAMs may be a major component of the tumour microenvironment and are directly involved in tumour growth, infiltration, and metastasis.…”
mentioning
confidence: 99%
“…A number of studies have shown that the expression of certain stress proteins (including heat shock proteins and C-reactive proteins) are increased during HBV infection (33,34). Moreover, these proteins may affect macrophage activation (35,36). Therefore, it was speculated that the expression of macrophage miR-210 may be affected by these stress proteins or other unknown factors during HBV infection.…”
Section: Discussionmentioning
confidence: 99%